Reticulospinal function can be measured in the tibialis anterior using the StartReact method - Oliver Hayman; Elliott Atkinson; Paul Ansdell; Luca Angius; Kevin Thomas; Glyn Howatson; Dawson J. Kidgell; Jakob Škarabot; Stuart Goodall (Advanced Exercise and Health Science)
The neurophysiology of dorsiflexor motor pools are highly studied, with previous work showing adaptations in corticospinal tract function, but little is known about the responsiveness of the reticulospinal tract (RST). Specifically, it is unknown if RST function can be measured indirectly in the tibialis anterior (TA). RST function was quantified using the StartReact protocol whereby dorsi flexor contractions were performed ‘as fast as possible’ in response to visual (VRT), visual auditory (VART; 80 dB), or visual-startling (VSRT; 110 dB) cues; with reaction time and the rate of torque development (RTD) calculated. We assessed the reproducibility of responses on two separate days separated by 3 weeks. Reaction times were faster during VSRT vs. VART during both visits (−7 ms; P < 0.001) confirming a StartReact effect. During the StartReact assessment, voluntary torque (F2,22 = 66.75, P < 0.001) and RTD over 50 (F2,22 = 22.02, P < 0.001) and 100 ms (F2,22 = 30.81, P < 0.001) increased in a stepwise manner (i.e., VSRT vs. VART vs. VRT). A good level of reliability was evident for assessment of reaction times (TE range 7–9%; ICC2,1 range 0.68 – 0.77), but measures of the VART−VSRT difference and RST Gain (TE, ≥23%; ICC2,1, ≤0.54), along with absolute and relative RTD (TE ≥19%; ICC2,1 ≤0.82) showed poorer levels of reliability. In conclusion, the StartReact method can be used to measure RST function in the TA, albeit the magnitude of this effect is small and aspects of between day reliability are poor.